KARAKTERISTIK LAHAN DAN KONSTRUKSI TABEL KEBUTUHANNYA BAGI PENGEMBANGAN ATUNG (Parinarium glaberimum Hassk) DI NEGERI HARUKU - Magdalena V Ferdinandus; Conradus Ufie; Simson Liubana (JURNAL BUDIDAYA PERTANIAN, 2017)
This research was conducted on sample area where Atung plant grow, focused on the Land â€œPetuananâ€ of â€‹â€‹Haruku village in Haruku small Island-Central Maluku Regency, from December 2016 till May 2017. The aims of this research were: 1) to assess the physical characteristics of land affecting the growth and production of Atung plant at the study area; 2) to elaborate the physical essential information and necessary data on the basis of literature and field review in constructing the land suitability table for the Atung Plant (as a preliminary approach); 3) to implement or test the appropriate land suitability table for the land suitability evaluation of Atung based on available biophysical land characteristic data. The method used in this study was a library study and field survey using the distance of flexible transect observation in accordance with the conditions where Atung grows. The results of this study consisted of the land characteristics data for Atung plant; i.e. climate, topography, and soil. The study of land characteristics obtained from the literature, field review and knowledge of the local community and construction of the land suitability table for Atung, an appropriate test in the Waai village showed that the land suitability category as the S3 class with the limiting factor was pH value that was easily improved and upgraded to the suitability class of S2/S1.